EFEKTIVITAS MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAME GENIALLY TERHADAP PENINGKATAN KESADARAN DEMOKRASI PESERTA DIDIK DALAM PENDIDIKAN PANCASILA DI SMA NEGERI 2 BANDUNG - Rahmatika, Silna; Sundawa, Dadang; Sartika, Rika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of Genially-based interactive learning media in enhancing students’ democratic awareness in the Pancasila Education course at Bandung State High School 2. The study employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The sample consisted of two classes: Class XI-D, the experimental class using the Genially game-based learning media, and Class XI-K, the control class using video-based media, selected through purposive sampling. The research instruments included affective essay questions (pretest-posttest) and a 5-point Likert scale questionnaire. Data were analyzed using descriptive statistics, simple linear regression, and the coefficient of determination via SPSS version 25. The results showed that the experimental class experienced an increase in democratic awareness of 21.36 points (from an average of 57.97 to 79.33), significantly higher than the control class, which increased by only 6.94 points. The simple linear regression test yielded a correlation coefficient of R = 0.634 (strong correlation), a calculated F-value of 18.822 (sig. 0.000 < 0.05), and a coefficient of determination of R² = 0.402, indicating that the Genially game contributed 40.2% to the increase in students’ democratic awareness. These findings demonstrate that Genially-based learning media is significantly more effective in enhancing students’ democratic awareness than video-based media.